Jeff Gordon : running up front - Cain, Anthony B., 1967- (Chicago Triumph Books, 2003)
Presents a brief biography and summary of the accomplishments of NASCAR champion Jeff Gordon.
Keywords: Gordon, Jeff, -- 1971-; Automobile racing drivers -- United States -- Biography; Automobile racing drivers